2023
DOI: 10.1007/s00395-023-00977-4
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase A-dependent ROS formation modulates human cardiomyocyte differentiation through AKT and WNT activation

Abstract: During embryonic development, cardiomyocytes undergo differentiation and maturation, processes that are tightly regulated by tissue-specific signaling cascades. Although redox signaling pathways involved in cardiomyogenesis are established, the exact sources responsible for reactive oxygen species (ROS) formation remain elusive. The present study investigates whether ROS produced by the mitochondrial flavoenzyme monoamine oxidase A (MAO-A) play a role in cardiomyocyte differentiation from human induced pluripo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Since most ROS are generated from chondriosome [ 21 ], breaking its balance in tumor cells has become an effective strategy for the development of anticarcinogen [ 22 ]. To further illuminate the relationship between nebivolol-induced apoptosis and mitochondria, ROS level was determined in melanoma cells exposed to nebivolol (0–10 μM) for 24 h. Consequently, the unequivocal enhancement effect on ROS levels was presented in a concentration-dependent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since most ROS are generated from chondriosome [ 21 ], breaking its balance in tumor cells has become an effective strategy for the development of anticarcinogen [ 22 ]. To further illuminate the relationship between nebivolol-induced apoptosis and mitochondria, ROS level was determined in melanoma cells exposed to nebivolol (0–10 μM) for 24 h. Consequently, the unequivocal enhancement effect on ROS levels was presented in a concentration-dependent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the regulatory effect of β-catenin on cardiomyocyte proliferation may also be related to the Hippo pathway ( Heallen et al, 2011 ). In mouse embryonic hearts, Hippo pathway inactivation results in heart enlargement, resulting in increased cardiomyocyte quantity and cardiomyocyte proliferation ( Heallen et al, 2011 ; Di Sante et al, 2023 ). The expression of β-catenin was upregulated in this heart, and deleting one copy of β-catenin could rescue the cardiac overgrowth phenotype.…”
Section: The Role Of β-Catenin In Cardiac Development and Functionmentioning
confidence: 99%
“…Recently, our research group discovered a specific context in which the formation of ROS dependent on MAO is crucial for triggering signaling pathways and ensuring the correct differentiation of cardiomyocytes [ 19 ]. To investigate the hypothesis that ROS generated by MAOs play a direct role in regulating human cardiac specification, we conducted experiments to observe whether MAO-A contributes to mitochondrial ROS formation during the differentiation of human induced pluripotent stem cells (hiPSCs) into cardiomyocytes (hiPSC-CMs).…”
Section: Mao Involvement In Cardiac Physiologymentioning
confidence: 99%
“…To investigate the hypothesis that ROS generated by MAOs play a direct role in regulating human cardiac specification, we conducted experiments to observe whether MAO-A contributes to mitochondrial ROS formation during the differentiation of human induced pluripotent stem cells (hiPSCs) into cardiomyocytes (hiPSC-CMs). Of note, MAO-A appears to be the predominant isoform expressed in the hiPSCs, whereas MAO-B is absent and appears only after 40 days of differentiation, in mature hiPSC-CMs [ 19 ]. Our findings revealed that hiPSC-CMs with MAO-A knockout or knockdown exhibited impaired sarcomere structure and function, along with reduced levels of mitochondrial ROS.…”
Section: Mao Involvement In Cardiac Physiologymentioning
confidence: 99%